In Situ Observations of Phase Changes in Shock Compressed Forsterite - M. G. Newman; R. G. Kraus; M. C. Akin; J. V. Bernier; A. M. Dillman; M. A. Homel; S. Lee; J. Lind; J. L. Mosenfelder; D. C. Pagan; N. W. Sinclair; P. D. Asimow (Geophysical Research Letters)
Abstract Shockwave data on mineral‐forming compounds such as Mg2SiO4 are essential for understanding the interiors of Earth and other planets, but correct interpretation of these data depends on knowing the phase assemblage being probed at high pressure. Hence, direct observations of the phase or phases making up the measured states along the forsterite Hugoniot are essential to assess whether kinetic factors inhibit the achievement of the expected equilibrium, phase‐separated assemblage. Previous shock recovery experiments on forsterite, which has orthorhombic space group Pbnm, show discrepant results as to whether forsterite undergoes segregation into its equilibrium phase assemblage of compositionally distinct structures upon shock compression. Here we present the results of plate impact experiments on polycrystalline forsterite conducted at the Dynamic Compression Sector of the Advanced Photon Source. In situ X‐ray diffraction measurements were used to probe the crystal structure(s) in the shock state and to investigate potential decomposition into periclase and bridgmanite. In contrast to previous interpretations of the forsterite shock Hugoniot, we find that forsterite does not decompose but instead reaches the forsterite III structure, which is a metastable structure of Mg2SiO4 with orthorhombic space group Cmc21.